Shewanella putrefaciens bacteraemia associated with terminal ileitis - Yiallouros, Panayiotis K.; Mavri, Antonia; Attilakos, Achilleas V.; Moustaki, Maria; Leontsini, Fani; Karpathios, Themistocles (My University, 2013)
Shewanella putrefaciens has a wide geographical distribution, including sea- and fresh water, fish and soil, but it is an unusual pathogen in humans. A previously healthy boy without known immunodeficiency presented with fever, abdominal pain and diarrhoea, and a mass in the right lower quadrant. Terminal ileitis was confirmed by MRI and Shewanella putrefaciens was isolated from two separate blood cultures. This is the first report of terminal ileitis associated with Shewanella putrefaciens septicaemia.
Keywords: Bacteraemia; Shewanella putrefaciens; Terminal ileitis